PENGEMBANGAN MEDIA PEMBELAJARAN MOBILE LEARNING BERBASIS ANDROID PADA TEMA 7 PERISTIWA DALAM KEHIDUPAN DI KELAS V SDN 2 KENITEN - Hidayah, Nisrina Ajrina Nur; Pamujo, Pamujo; Badarudin, Badarudin (Lentera: Jurnal Ilmiah Kependidikan, 2019)
This study is a research and development which aims to develop Thematic Apps applications in the form of android mobile learning media for elementary school students. This development research was carried out using the Four-D model, namely define, design, develop, and disseminate. Media validation is carried out by three experts, namely media experts, material experts, and linguists. The media developed is tested in a limited and broad manner. Limited trials were conducted in the fifth grade of Keniten 2 Public Elementary School while extensive trials were conducted in Windujaya Public Elementary School and Karangnangka Public Elementary School. Based on the assessment of material experts, media experts, and linguists obtained an average score on the material aspects of 72.5 (Fairly Worthy), on the media aspect of 85.5 (Very Worthy), and on the language aspect by 75.0 (Worth ) Based on the response from two class V teachers, it showed that the average score of respondents 1 was 98.46% and from respondents 2 that the average score reached 83.08% with the category "Very Worthy". Based on the response of students in the development test obtained an average score on the repodusibility coefficient reaches an average of 0.5 while the scalbility coefficient reaches an average of 1.0 with the category "Very Eligible". The results of the validation test for improving student achievement are conducted using pretest and posttest obtained a gain value of 0.5 classified (Moderate).